2012
DOI: 10.1016/j.jbi.2012.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Avatar-based simulation in the evaluation of diagnosis and management of mental health disorders in primary care

Abstract: Major Depressive Disorder (MDD) and Posttraumatic Stress Disorder (PTSD) are highly prevalent illnesses, but the literature suggests they are under-detected and suboptimally managed by primary care practitioners (PCPs). In this paper, we propose and use an evaluation method, using digitally simulated patients (avatars) to evaluate the diagnostic and therapeutic reasoning of PCPs and compared it to the traditional use of paper-based cases. Verbal (think-aloud) protocols were captured in the context of a diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…This research provides a foundation for improving delivery of care. Of particular relevance to the current study, is that expert subjects were better able to selectively attend to information relevant to the generation of a correct diagnostic solution than the resident PCPs and seasoned faculty PCPs (amongst other findings; Satter et al, 2012). Research in clinical text comprehension suggests that selective recall of relevant information is a defining characteristic of expertise (Patel & Groen, 1991).…”
Section: Report On Mental Health (Us Department Of Health and Humanmentioning
confidence: 63%
See 4 more Smart Citations
“…This research provides a foundation for improving delivery of care. Of particular relevance to the current study, is that expert subjects were better able to selectively attend to information relevant to the generation of a correct diagnostic solution than the resident PCPs and seasoned faculty PCPs (amongst other findings; Satter et al, 2012). Research in clinical text comprehension suggests that selective recall of relevant information is a defining characteristic of expertise (Patel & Groen, 1991).…”
Section: Report On Mental Health (Us Department Of Health and Humanmentioning
confidence: 63%
“…Results indicated that PCPs, overall, did not perform as well as the experts in diagnosing and treatment planning (Satter et al, 2012). In some instances it appeared as though the PCPs from the text-based group were able to recall more and draw inferences more often than the PCPs in the avatar simulation group.…”
Section: Report On Mental Health (Us Department Of Health and Humanmentioning
confidence: 86%
See 3 more Smart Citations